Organismal and Molecular Malacology - Ray, Sajal (IntechOpen, 2017)
The book with two sections represents the current trend of research in basic and applied malacology. In the section "Organismal Malacology", high-impact articles were contributed in the frontier areas of taxonomy, ecology and aquaculture of molluscs. Importance of mussel in water quality monitoring was highlighted. Biology and conservation of keystone molluscs were discussed from organismal point of view. "Cellular and Molecular Biology" section contains informative chapters on toxin-induced differential gene expression, spatiotemporal neural activity in olfactory processing in slug and immunity of hydrothermal vent molluscs. Biochemistry of cellulose degradation, lipid profile and C-reactive protein were elucidated in detail in separate chapters. This book represents a rich source of malacological information for the scientists, teachers and students.